2008
DOI: 10.1021/nn800264q
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Polyol Route to Uniform Gold Octahedra with Tailorable Size and Their Optical Properties

Abstract: A straightforward and effective polyol route for the controllable synthesis of high-quality gold (Au) octahedra with uniform size is presented in an ethylene glycol solution. Large-scale Au octahedra with the size ranging from tens to hundreds of nanometers were selectively synthesized in high-yield. The surfaces of octahedral Au nanocrystals are smooth and correspond to {111} planes. Formation of Au nanooctahedra was attributed to the preferential adsorption of cationic surfactant poly(diallyldimethylammonium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
241
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(251 citation statements)
references
References 50 publications
9
241
0
1
Order By: Relevance
“…The application of such adsorbing polymers as stabilizers or additives during the synthesis actively infl uences the optical properties of the resulting gold nanoparticles, through morphology control, as shown in Figure 4 . It is believed that the selective adsorption of such polymers (or surfactants, ions and other ligands) on certain crystalline facets can inhibit the growth along specifi c directions, leading to anisotropic growth [110] . Therefore, by selecting a stabilizing agent with a certain selective adsorption or introducing an additive together with the stabilizing agent in the reaction that displays surface-regulating properties, anisotropic nanocrystals can be synthesized in a solution phase.…”
Section: Physically Adsorbed Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of such adsorbing polymers as stabilizers or additives during the synthesis actively infl uences the optical properties of the resulting gold nanoparticles, through morphology control, as shown in Figure 4 . It is believed that the selective adsorption of such polymers (or surfactants, ions and other ligands) on certain crystalline facets can inhibit the growth along specifi c directions, leading to anisotropic growth [110] . Therefore, by selecting a stabilizing agent with a certain selective adsorption or introducing an additive together with the stabilizing agent in the reaction that displays surface-regulating properties, anisotropic nanocrystals can be synthesized in a solution phase.…”
Section: Physically Adsorbed Polymersmentioning
confidence: 99%
“…Therefore, Cho et al introduced a straightforward polyol process using the polyelectrolyte PDDA as stabilizer rather than the traditional PVP [110] . High-yield ( > 95 % , without purifi cation), monodisperse Au octahedra were obtained in a one-pot reaction with a short reaction time.…”
Section: Physically Adsorbed Polymersmentioning
confidence: 99%
“…We found that the final outcome in terms of the nanoparticle size is affected by the initial growth phase, likely as a result of relatively small changes to the reaction temperature. Lower temperatures lead to a slower rate of reduction of the gold salt, producing larger polyhedral crystallites 15 and consequently larger ultrasmooth NPs after the etching step. We prepared US gold NPs of 50 nm and 100 nm in diameter.…”
Section: A Ultrasmooth Gold Nanoparticle Synthesismentioning
confidence: 99%
“…8 During the past years, great effort has been contributed to design new procedures dealing with the synthesis of anisotropic gold nanostructures such as nanoplates, 9 nanorods, 10 nanocubes 11 and polyhedra 12 with well-controlled sizes and shapes. However, the preparation of nanostructures with novel and controllable shapes and promising features is still a challenge for materials researchers.…”
Section: Introductionmentioning
confidence: 99%